2008
DOI: 10.1109/vetecs.2008.355
|View full text |Cite
|
Sign up to set email alerts
|

A New Duplex without Loss of Data Rate and Utilizing Selection Diversity

Abstract: This paper presents a new duplex approach which does not require guard resources suitable for indoor 2 × 2 MIMO environments. In the proposed duplex, two virtual channels in the spatial domain are generated by precoding and postcoding MIMO channels, not to use guard resources in either the time or frequency domain. In addition, this system can achieve selection diversity since the generation of virtual channels is not unique for the given channels information. We will show the generation of the virtual channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 8 publications
0
33
0
2
Order By: Relevance
“…After some mathematical manipulations similar to the case of T 2 , an approximate expression for T 3 is finally given as in (9).…”
Section: Appendix a Approximate Calculation For The Outage Probabilitmentioning
confidence: 99%
See 1 more Smart Citation
“…After some mathematical manipulations similar to the case of T 2 , an approximate expression for T 3 is finally given as in (9).…”
Section: Appendix a Approximate Calculation For The Outage Probabilitmentioning
confidence: 99%
“…Reports in [6][7][8] have shown that, through the combined use of passive and active (analog and digital) cancellation techniques, the self interference can be reduced to strikingly low values. Indeed, [6] shows that an average cancellation of 74 dB leads to higher FD rates if compared with HD rates, by using active cancellation to attenuate the line-of-sight (LOS) component of the self interference [9]. In this sense, the last advances in full-duplex transmission have generated great expectations, mainly for the spectral efficiency advantages, not only in cooperative networks, but for bidirectional communications or backhauling and access links in emerging wireless communication technologies for 5G [10,11].…”
mentioning
confidence: 99%
“…This is meaningful because beamforming and full rank transmission capture the low and high SNR properties of those systems, respectively. By comparing the UB in (13) and the LB in (14), it is possible to evaluate sufficient conditions for a B-MIMO system to have greater achievable rate than a U-MIMO system more easily. Later in this section, those conditions are evaluated by comparing these bounds.…”
Section: B Sufficient Conditions Under Which the B-mimo System Outpementioning
confidence: 99%
“…On the other hand, a conventional MIMO system is called a uni-directional MIMO (U-MIMO) system because the spatial resources are used for uni-directional data transmission. The concept of a B-MIMO system has been used in research regarding duplexing systems [13] [14] and various relay systems [15]- [18]. In those studies, bi-directional use of the spatial resources is primarily investigated from the perspective of the achievable rate of those systems when the channels are in a spatially white environment.…”
mentioning
confidence: 99%
“…In theory, FD systems are capable of doubling the overall spectral efficiency when compared to the traditional Half-Duplex (HD) networks. Unfortunately, the performance of practical systems is severely deteriorated by the intrinsic Self-Interference (SI) and the extra CoChannel Interference (CCI) from other concurrent (sametype) transmitters [5].…”
Section: Introductionmentioning
confidence: 99%